Is subcranial Le Fort III plus Le Fort I osteotomy stable? - Jorge Boos Lima, Fernanda Brasil Daura; Vieira, Eduardo Hochuli [UNESP]; Juergens, Philipp; Lima Junior, Sergio Monteiro (Churchill Livingstone, 2017)
The purpose of this study was to test whether associated subcranial Le Fort III (sLF III) and Le Fort I (LF I) osteotomies are stable after large advancements of the middle third of the face and maxilla. The authors designed a retrospective study and enrolled a sample of consecutive patients with midface hypoplasia treated with associated sLF III and LF I osteotomies in this IRB-approved study between September 2013 and February 2015. To test whether the long-term stability was satisfactory, the authors compared cephalometric changes from immediately after surgery to 18 months after surgery taken from multi-slice computed tomography using two different third-party imaging software programs. Statistical significance was set as P = 0.05. The sample comprised 11 patients (mean age 23.84 +/- 4.17 yr; 54% men). The mean advancement of the upper incisor immediately after surgery was 10.03 +/- 1.6 mm. After 18 months, the position of the upper incisor did not vary significantly (10.18 +/- 2.35 mm). All other cephalometric landmarks did not present statistically significant differences between immediately after and 18 months after surgery, with horizontal and vertical variations of less than one millimetre. This study supports that sLF III and LF I osteotomies are effective in maintaining stable horizontal and vertical skeletal positioning after surgery. (C) 2017 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Orthographic surgery; Le Fort III osteotomy; Stability